From Hardships to Possibilities: Dissertation Writing during the COVID-19 Pandemic (Comparative & International Education Series, 2021)
In an attempt to mitigate community spread of COVID-19, many universities canceled face-to-face sessions and shifted to online instruction. For advanced doctoral students, this sudden shift welcomed new hardships as they began to collect data for their qualitative dissertation studies. This change called for students and their supervising professor to revisit IRB (Institutional Research Board) protocols as interviews, focus groups and observations techniques were now impossible. In this chapter, we discuss how social distancing measures created new possible ways for students to gather rich, quality data from communication technology platforms. This new digital approach of engaging participants in meaningful discussions welcomed new possibilities for doctoral students to recruit participants for a more global context. This chapter will offer strengths, challenges, and new ways of knowing for future studies.How to cite this chapter:Niño, J. M., & Martínez, O. M. (2022). From hardships to possibilities: Dissertation writing during the COVID-19 pandemic. In  R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 80-92). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/